RETRACTED : Effect Of Financial Ratio and Company Size on Profit Growth in Industrial Variety Sector Companies Listed in Indonesia Stock Exchange 2015-2017 Period - Sella Saulinda; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to analyze the influence of the current ratio, inventory turnover, debt to equity, and company size on profit growth in various sub-industry companies listed on the Indonesian stock exchange. The sample in this study were 22 companies for the research period of 2015-2017, with the sampling method used purposive sampling. The test used in this study is the classic assumption test (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), multiple linear regression is used as an analysis tool and to test the hypothesis used t-test, f-test and R² test. The linear regression equation answers Y = -60.03827 + 23.127291X1 + 9.931366X2 + 7.706515X3 - 2.907177X4. The results of the study show that there is a positive and significant influence between the Current ratio on earnings growth, indicating that poor company liquidity will affect the decline in the value of profits in various sub-industry companies. Inventory Turnover has a positive and significant effect indicating the effectiveness of inventory turnover to increase profit growth in various sub-industry companies. Debt to Equity and company size have no effect on profit growth in various industrial Sub companies listed on the Indonesia stock exchange.